Pengaruh Customer Relationship Management (CRM), Desain Produk dan Kualitas Pelayanan terhadap Kepuasan Pelanggan Swarovski Galaxy Mall Surabaya - Safitri, Elly Dwi; Pratiwi, Ni Made; Maduwinarti, Ayun (Jurnal Dinamika Administrasi Bisnis, 2021)
ABSTRACTCustomers are one of the valuable assets for the company, especially because loyal customers tend to have a fairly high commitment to the level of customer satisfaction. Maintaining customer satisfaction is not easy nowadays because there are many competitors in the same field. Thus, conditions like this make the company always evaluate feedback from customers so that the company can retain customers. So the author is interested in the research title "The Influence of Customer Relations Management (CRM), Product Design and Service Quality on Customer Satisfaction at Swarovski Galaxy Mall Surabaya. The purpose of this study to determine the effect of Customer Relationship Management (CRM), product design, service quality on customer satisfaction in buying Swarovski in Galaxy Mall Surabaya. This research is quantitative approach. Samples method using a purpose sample techniq that is determine samples with consideration or certain criteria. The number  samples for this researches are 100 respondent. The data coleccting technique is questionaire by Google Drive Form in order fielled by respondent. This research shows the results that Customer Relationship Management (CRM), product design, service quality have a positive and significant effect on customer satisfaction. Keywords: Customer Relationship Management (CRM), design product, and service quality, customer satisfaction.